Exploring new models for improving planetary rover operations efficiency through the 2016 CanMars Mars Sample Return (MSR) analogue deployment. (January 2019) - Pilles, Eric A.; Cross, M.; Caudill, C.M.; Francis, R.; Osinski, G.R.; Newman, J.; Battler, M.; Bourassa, M.; Haltigin, T.; Hipkin, V.; Kerrigan, M.; McLennan, S.; et al.
Abstract: Approaches to rover mission operations were investigated in the framework of the CanMars Mars Sample Return (MSR) analogue mission deployments. Improving the efficiency of operations is a necessity for future planetary missions, including Mars 2020, which seek to combine sample targeting with in situ investigations in the fixed amount of time available in primary science operations and with increasingly high public and science community expectations for results. Analogue missions provide an important opportunity to experiment with mission operation strategies and learn lessons that can be incorporated in future missions. Improving the efficiency of operations was a key objective of the 2015 and 2016 CanMars mission deployment. The mission overall operations organisation for CanMars is described with comparison to current implementation of Mars Exploration Rover and Mars Science Laboratory missions. Approaches being tested included 3-sol plan sequences with increased use of waypoints for teach and return as part of a global Walkabout approach, use of Strategic Observation days to focus the Science Team's efforts, and consideration to improvements in how information is exchanged tactically and strategically in operations. Highlights: Rover mission operation strategies are tested during an analogue mission in Utah. Fully pre-developed strategic traverse plans were prepared days ahead of time. Consecutive multi-sol plans were executed with increased autonomous capabilities. Post-drive autonomous target selection greatly enhances the value of multi-sol plans. A "walkabout-first" strategy allowed for rapid determination of potential targets.